Efektivitas Model Problem-Based Learning pada Mata Pelajaran Instalasi Motor Listrik - Linda Sri Wahyuni; Sukardi Sukardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This study aims to determine the effectiveness of the Problem-Based Learning learning model on student learning outcomes in the subject of Electric Motor Installation class XI TITL at SMK Negeri 1 Rao Selatan. It is difficult for students to obtain learning outcomes according to predetermined standards because the teacher dominates learning activities so that students do not actively participate during the learning process. This research is using experimental method. The research design is a Pre-Experimental Design with the form used by One Group Pretest Posttest. The subjects in the study were students of class XI TITL at SMK Negeri 1 Rao Selatan for the 2022/2023 academic year with a total of 26 people. The research instruments used were pretest and posttest questions, attitude assessment, and skills assessment. The data obtained from the pretest and posttest results were analyzed using the analysis of the learning completeness of the students so that the number of students whose scores were above the KKM in the posttest was obtained more than in the pretest. Data on the attitudes and skills of students were analyzed using attitude competency assessment and skills competency assessment so that student scores were already at the predicate A (very good) and B (good). Thus, the Problem-Based Learning model is effective in increasing student learning outcomes in the subject of Electric Motor Installation class XI TITL at SMK Negeri 1 Rao Selatan.